2014
DOI: 10.21103/article4_3_er1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Respiration of Rat Cardiomyocytes and Soleus Muscle Fibers under Ultra-Short-Term Antiorthostatic Suspension

Abstract: The aim of the study was to analyses rat soleus fibers and left ventricle (LV) cardiomyocyte cell respiration after 6, 12, 18, 24 and 72 hours of antiorthostatic suspension by the tail. We measured V 0-basal oxygen consumption rate, V Glu+Mal-respiration velocity over a catalyst of malate and glutamate (5 mM glutamate + 2 mM malate) and V max-maximal respiratory rate (in the presence of 1 mM ADP) using the Saks polarography technique. We also determined the cytochrome c content and expression of its gene (Cycs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…This transient accumulation could lead to the activation of STAT3 and an increase in the rate of cellular respiration (Figure 5). Moreover, we observed the dissociation of alpha-actinin-1 and an increase in the rate of cellular respiration in the heart muscle when simulating microgravity in rats [22,39]. Furthermore, the content of alpha-actinin decreased with the decreasing content of actin, which we also observed in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…This transient accumulation could lead to the activation of STAT3 and an increase in the rate of cellular respiration (Figure 5). Moreover, we observed the dissociation of alpha-actinin-1 and an increase in the rate of cellular respiration in the heart muscle when simulating microgravity in rats [22,39]. Furthermore, the content of alpha-actinin decreased with the decreasing content of actin, which we also observed in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…The motor activity of sperm is determined by the state of the microtubule cytoskeleton, which provides motility, and its energy supply. Previous studies showed that a decrease in the mechanical load on skeletal muscle cells leads to a decrease in the efficiency of cell respiration [ 12 , 13 , 14 , 15 , 16 ] and an increase in the volume mechanical load, particularly on cardiomyocytes, to an increase in the rate of energy production [ 14 ]. Therefore, we hypothesized that the observed changes in motility may be associated with changes in cell respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are data demonstrating that alpha-actinin-4 dissociates from the cortical cytoskeleton into the cytoplasm in the soleus muscle cells at the earliest stages (6 hours) of hindlimb suspension [ 17 ]. Furthermore, subsequently, there are alterations in the mRNA content of the alpha-actinin-4 and decrease in gene expression of cytochrome c (one of the basic in cell respiration) [ 18 ]. However, we can suggest that such dynamics may be typical not only for the alpha-actinin-4, but also for other actin-binding proteins like as proteins of the Arp2/3 complexes, tropomodulin, supervillin, L-plastin.…”
Section: Introductionmentioning
confidence: 99%